2020
DOI: 10.1093/neuros/nyaa055
|View full text |Cite
|
Sign up to set email alerts
|

Scoliosis Research Society-Schwab Grade 6 Osteotomy for Severe Congenital Angular Kyphoscoliosis: An Analysis of 17 Cases With a Minimum 2-Year Follow-up

Abstract: BACKGROUND For some patients with severe congenital angular kyphoscoliosis (SCAK), 1-level vertebral column resection is insufficient and the Scoliosis Research Society (SRS)-Schwab Grade 6 osteotomy may be necessary. However, the indications and clinical outcomes of SRS-Schwab Grade 6 osteotomy in patients with SCAK have not been investigated in depth. OBJECTIVE To investigate the middle-term radiographic and clinical outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The mean Cobb angle of the main curve and horizontal distance between the C7 plumb line and central sacral vertical line were 96.1° 16.7°and 40. 4 (P < 0.001), with no evidence of correction loss during follow-up (P < 0.05). Patients with type 3 spinal cord exhibited a larger Cobb angle of the main curve than those with type 1 or 2 spinal cord (P < 0.001).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The mean Cobb angle of the main curve and horizontal distance between the C7 plumb line and central sacral vertical line were 96.1° 16.7°and 40. 4 (P < 0.001), with no evidence of correction loss during follow-up (P < 0.05). Patients with type 3 spinal cord exhibited a larger Cobb angle of the main curve than those with type 1 or 2 spinal cord (P < 0.001).…”
Section: Resultsmentioning
confidence: 94%
“…The correction rate has significantly improved in the last decades due to the broader adoption of the three-column osteotomy (3CO). [1][2][3][4] However, the prospect of neurological deficits following these surgeries remains a significant concern. Previous studies have reported relatively high incidences (ranging from 9.9% to 17.4%) of neurological deficits during 3CO, [5][6][7][8] highlighting the need for a precise risk assessment.…”
mentioning
confidence: 99%
“…In the severe group, the average Cobb angle decreased from 104° to 33°, and the correction rate was up to 67%. Shi et al 16 also found a 65% correction rate in the treatment of severe scoliosis with the VCR technique. In addition to the surgery-only strategy, several researchers applied preoperative traction with posterior surgical correction.…”
Section: Discussionmentioning
confidence: 95%
“…The authors concluded that most patients would show varying degrees of IONM loss with the VCR procedure almost complete. Shi et al 12 reported 17 patients with severe congenital angular kyphoscoliosis undergoing multiple VCRs, and the alarming changes in IONM were detected in 4 patients (23.5%) during osteotomy. In the current study, the total incidence of IONM alters was 17.8% (98 of 551 patients) including 82 SEP alerts and 91 MEP alerts, which was slightly lower than the data from studies mentioned above.…”
Section: Discussionmentioning
confidence: 99%